2022
DOI: 10.1109/access.2022.3192838
|View full text |Cite
|
Sign up to set email alerts
|

Greening, Pricing and Marketing Coordination for a Complex Three-Level Supply Chain Under the Carbon Tax in China

Abstract: This paper examines a complex supply chain consisting of a raw material manufacturer, a consumer goods fabricator, a retailer and an end user. A sequential decision game model is constructed under carbon tax regulation, considering multiparty green technology innovation and green product marketing efforts in the supply chain. Using a backward-induction analysis process, the Nash equilibria of the game are obtained. With the help of numerical simulation, the sensitivity analysis of the key parameters affecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Another study on supply chain management showed that sustainable supply chain management can be considered appropriate for attracting the attention of consumers [48,49]. The results revealed that collaborating with suppliers could lead to positive outcomes, as GSCM practice can increase economic performance and create a competitive advantage for firms [50].…”
Section: Green Supply Chain Management For Effective Firm Performancementioning
confidence: 99%
“…Another study on supply chain management showed that sustainable supply chain management can be considered appropriate for attracting the attention of consumers [48,49]. The results revealed that collaborating with suppliers could lead to positive outcomes, as GSCM practice can increase economic performance and create a competitive advantage for firms [50].…”
Section: Green Supply Chain Management For Effective Firm Performancementioning
confidence: 99%